The day-of-the-week effect: the civets stock markets case (2013)
Finding patterns in the behavior or performance of financial markets has been a subject of interest for both analysts and academics. We use GARCH and IGARCH models with covariates to estimate the day- of-the-week (DOW) effect on both volatility and daily returns of the stock exchange markets for the CIVETS. We found a DOW effect on the daily returns for all of the CIVETS’ stock markets. DOW effect was also found for the daily returns’ volatility of some of the stock markets. Finally, there is evidence of lags in the DOW effect for the stock markets we analyze.